Evaluation of Archery Achievement Development Program for People with Disabilities in South Kalimantan - Utomo, Utomo (Angstrom Centre of Education, 2023)
This study aims to evaluate the National Paralympic Committee (NPC) program in fostering archery achievement for people with disabilities in the Province of South Kalimantan. This research focuses on the stages of planning, organizing, implementing and monitoring, evaluating and outcome or the role of the government towards the outstanding athletes. This study uses evaluation research methods through quantitative and qualitative approaches that combine the CIPP model from Stufflebeam and Stake model in the outcome section. This study shows the results of achievement with indicators: 1) the context component (planning stage) shows quite effective results, 2) the input component (organizing stage) shows effective results, 3) the process component (implementation and supervision stage) shows effective results, 4) product components (evaluation stage) show the results are quite effective, 5) the outcome component (output/role of the government towards athletes who have achieved) shows effective results.